2019
DOI: 10.1093/eurheartj/ehz753
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal cardiopulmonary resuscitation in out-of-hospital cardiac arrest: a registry study

Abstract: Aims Out-of-hospital cardiac arrest (OHCA) without return of spontaneous circulation (ROSC) despite conventional resuscitation is common and has poor outcomes. Adding extracorporeal membrane oxygenation (ECMO) to cardiopulmonary resuscitation (extracorporeal-CPR) is increasingly used in an attempt to improve outcomes. Methods and results We analysed a prospective registry of 13 191 OHCAs in the Paris region from May 2011 to J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
148
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 196 publications
(154 citation statements)
references
References 36 publications
2
148
1
3
Order By: Relevance
“…The largest study to date on the use of ECPR for OHCA was recently published, shedding new light on the effectiveness of this approach. Bougouin et al [8] reported on 13,191 OHCA cases in metropolitan Paris. Of the 12,396 patients managed with conventional CPR, 1061 (8.6%) survived to hospital discharge, compared with 44 (8.4%) of 523 ECPR patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The largest study to date on the use of ECPR for OHCA was recently published, shedding new light on the effectiveness of this approach. Bougouin et al [8] reported on 13,191 OHCA cases in metropolitan Paris. Of the 12,396 patients managed with conventional CPR, 1061 (8.6%) survived to hospital discharge, compared with 44 (8.4%) of 523 ECPR patients.…”
mentioning
confidence: 99%
“…It is also important to study other medical interventions alongside ECPR such as early coronary revascularization [11,14]. The authors [8] suggested that ECPR for OHCA should be restricted to patients with shockable rhythms who achieve transient ROSC. This is important, given that shockable rhythms are a surrogate for the potential for revascularization.…”
mentioning
confidence: 99%
“…on extracorporeal cardiopulmonary resuscitation (CPR) in patients with an out-of-hospital cardiac arrest (OHCA) using extracorporeal membrane oxygenation (ECMO). 1 An important study in a field where mortality rates remain high and the search for the best therapy and patient selection continues. In the largest ECMO registry to date, there were 13 191 patients who received resuscitation for OHCA of presumed cardiac cause and included 525 patients (4%) managed with extracorporeal-CPR because sustained return of spontaneous circulation (ROSC) was not achieved.…”
mentioning
confidence: 99%
“…Among patients treated with extracorporeal-CPR, 8.4% was discharged alive, compared with 8.6% in the conventional-CPR group. 1 This shows that we need to define better which patients might benefit the most from this therapy, such as patients with an initial shockable rhythm, transient ROSC, and limited delay.…”
mentioning
confidence: 99%
See 1 more Smart Citation